2009
DOI: 10.2337/dc09-0455
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rimonabant on Glycemic Control in Insulin-Treated Type 2 Diabetes: The ARPEGGIO Trial

Abstract: OBJECTIVETo examine the efficacy and safety of rimonabant, a selective cannabinoid receptor type-1 antagonist, in patients with type 2 diabetes receiving insulin monotherapy.RESEARCH DESIGN AND METHODSPatients (n = 368; A1C ≥7%) were randomized to 20 mg/day rimonabant or placebo in this 48-week, double-blind, placebo-controlled multicenter trial. Change in baseline A1C to week 48 (primary outcome) and changes in body weight, waist circumference, and lipid levels (secondary outcomes) were assessed.RESULTSRimona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 15 publications
2
25
1
4
Order By: Relevance
“…More patients achieved greater than 10% reduction in mean total daily insulin dose in the rimonabant group than in the placebo group. 12 However, our results indicated that G1359A polymorphism was not associated with the presence of T2DM, which indicated that this polymorphism may not increase the susceptibility for T2DM. Further studies are needed to explain whether this polymorphism contribute to the risk for T2DM.…”
Section: Discussioncontrasting
confidence: 54%
“…More patients achieved greater than 10% reduction in mean total daily insulin dose in the rimonabant group than in the placebo group. 12 However, our results indicated that G1359A polymorphism was not associated with the presence of T2DM, which indicated that this polymorphism may not increase the susceptibility for T2DM. Further studies are needed to explain whether this polymorphism contribute to the risk for T2DM.…”
Section: Discussioncontrasting
confidence: 54%
“…The efficacy and safety of Rimonabant in weight reduction and improving metabolic syndrome parameters in different populations have been assessed in several trials. The four large ‘Rimonabant in obesity’ (RIO) studies involved over 6600 participants, composed of four separate trials: RIO North America,[60] RIO Europe,[61] RIO Diabetes[62] and RIO Lipids,[63] in addition to other randomized double-blind Rimonabant-placebo controlled trials, namely the Serenade,[64] Stradivarius,[65] Arpeggio[66] and Adagio-lipids studies. [67]…”
Section: Role Of Cb1 Receptors In Fatty Liver Disease: (Clinical Evidmentioning
confidence: 99%
“…Rimonabant (SR141716A) is the first-in-class CB1 blocker for obesity treatment (Van Gaal et al, 2005). The data obtained from clinical trials suggest that rimonabant may have a beneficial effect against disrupted lipid metabolism in the liver (Després et al, 2005;Scheen et al, 2006;Hollander et al, 2010). However, the antisteatotic effect of rimonabant in hepatocytes and the molecular basis responsible for this action remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%